1999
DOI: 10.2139/ssrn.135410
|View full text |Cite
|
Sign up to set email alerts
|

Migration Across Spanish Provinces: Evidence from the Social Security Records (1978-1992)

Abstract: This paper uses Social Security records to study internal migration in Spain. This is the rst paper that uses this data source, which has some advantages with respect to existing data sources: it includes only job-seeking migrants and it allows to identify temporary migration.Within the framework of an extended gravity model, we estimate a Generalized Negative Binomial regression on gross migration ows between provinces. We quantify the e ect of local labor market imbalances on workers' mobility and discuss th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
17
0

Year Published

2004
2004
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(18 citation statements)
references
References 15 publications
(15 reference statements)
1
17
0
Order By: Relevance
“…Fortunately, provincial GDP per capita is provided by the Guglielmo Tagliacarne Institute (see Table 2). It is worth noting that GDP is often used in gravity models (Congdon, 1989;Shen, 1999;Devillanova & Garcìa Fontes, 2004) and, as in previous research, we expect that the higher the GDP in the destination, the higher the in-migration and the lower the out-migration. Conversely, the higher the unemployment rate in the origin the higher the out-migration (push factor) (DaVanzo, 1978).…”
Section: Datasupporting
confidence: 64%
See 1 more Smart Citation
“…Fortunately, provincial GDP per capita is provided by the Guglielmo Tagliacarne Institute (see Table 2). It is worth noting that GDP is often used in gravity models (Congdon, 1989;Shen, 1999;Devillanova & Garcìa Fontes, 2004) and, as in previous research, we expect that the higher the GDP in the destination, the higher the in-migration and the lower the out-migration. Conversely, the higher the unemployment rate in the origin the higher the out-migration (push factor) (DaVanzo, 1978).…”
Section: Datasupporting
confidence: 64%
“…The negative binomial model is nonlinear and is normally estimated using the maximum likelihood NewtonÁRaphson algorithm. The use of the negative binomial to model migration flows is relatively recent in the literature (see also Devillanova & Garcìa Fontes, 2004). In this paper we follow the approach of Hilbe (2007) in which, as in the majority of studies, the negative binomial model is considered as a derivation of a PoissonÁgamma mixture model with two parameters to be estimated (a and m), but it is also considered as a member of a single parameter exponential family distribution, such as generalized linear models (GLMs).…”
Section: Theoretical Framework and Empirical Methodologymentioning
confidence: 99%
“…However wages were not found to be a significant explanatory variable. Devillanova and Garcia Fontes (1998) testing for migration between provinces (a sub-regional category) found that pre-1986 migration was unresponsive to economic incentives (e.g. unemployment rate and employment growth differentials) but from 1986-1992 there was some response.…”
Section: Econometric Investigation Into the Explanatory Factors Causimentioning
confidence: 99%
“…Secondly labour markets in Spain have been characterised as rigid by many observers (Antonlin and Bover 1997;Bande et al 2007; Bande and Karanassou (forthcoming); Bentolila 1997Bentolila , 2001Devillanova and Garcia Fontes 1998;Fonseca 2003;JimenoSerrano and Bentolila 1997;Maza and Moral-Arce 2006). Wages have often been determined centrally by strong trade unions and marked segmentation of the labour market has existed for many years (Gil Martin 2004).…”
Section: Introductionmentioning
confidence: 99%
“…Examples are Pissarides & McMaster (1990) and Jackman & Savouri (1992) for British regions, Westerlund (1997) for the case of Sweden, as well as Bentolila & Dolado (1991) and Devillanova & Garcia-Fontes (2004) for Spanish regions. Only for Italian data Daveri & Faini (1998) point at a more prominent role given to regional wage levels in explaining gross out-migration from southern to northern regions.…”
Section: Literature Reviewmentioning
confidence: 99%